OTU-029 Faecal immunochemical tests (FIT) for surveillance after screening and polypectomy: an accuracy and efficiency study. (8th June 2018) - Robbins, Emma; Wooldrage, Kate; MacRae, Eilidh; Stenson, Iain; Patel, Bhavita; Pack, Kevin; Piggott, Carolyn; Pearson, Sheena; Snowball, Julia; Duffy, Stephen; Halloran, Stephen; Atkin, Wendy; et al.
Abstract : Introduction: Individuals at intermediate-risk for colorectal cancer (CRC) following adenoma removal within the English Bowel Cancer Screening Programme (BCSP) are invited for three-yearly surveillance colonoscopy. Given the invasive nature of colonoscopy and scarcity of endoscopy resources, there is a need for an alternative surveillance method. We aimed to determine whether annual testing with the faecal immunochemical test (FIT) is an effective alternative. Methods: Individuals aged 60–72 years and scheduled for surveillance following removal of intermediate-risk adenomas were recruited within the BCSP from January 2012 to December 2013. Quantitative FIT (OC-Sensor, Eiken) was offered at one, two, and three years post-polypectomy. Invitees who returned a completed consent form and an analysable FIT at Round 1 were included. Participants testing positive (≥40 µg haemoglobin (Hb)/g faeces) at Rounds 1 or 2 were offered early colonoscopy and were not invited to further FIT rounds. All other participants were offered the routine three-year surveillance colonoscopy. Diagnostic accuracy for CRC and advanced adenomas (AAs: adenomas≥10 mm, with tubulovillous or villous histology, or high grade dysplasia) was calculated at each round, using colonoscopy as the reference standard. We estimated diagnostic accuracy with lower haemoglobin thresholds and multiple rounds. Results: Of 8008 invitees, 5946 (74%) consented and returned an analysable FIT at Round 1. Uptake of FIT was higher (97%) in Rounds 2 and 3. FIT positivity decreased by round, from 6% to 4% in Rounds 1 to 3. In total, 26 participants were diagnosed with CRC and 443 with AAs. At 40 µg/g, sensitivity and specificity of the first FIT were, respectively, 31% and 94% for CRC and 18% and 95% for AAs. Sensitivities for CRC and AAs were higher, and specificities lower, with lower thresholds and multiple rounds. At 10 µg/g, the programme sensitivity and specificity of three rounds were, respectively, 85% and 71% for CRC and 57% and 73% for AAs. Conclusions: Annual low threshold FIT achieved relatively high sensitivity for CRC over three years. If this strategy replaced three-yearly surveillance colonoscopy, the number of colonoscopies could potentially be reduced by 70%. However, sensitivity for AAs was limited. Further research is needed to consider the implications for clinical practice of missing CRCs and AAs with FIT-based surveillance.